PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP DISIPLIN PEGAWAI PADA KANTOR BAPPEDA KABUPATEN PASAMAN - Hardinalis, Hardinalis (jurnal ekonomi, 2008)
The discipline work the officer very hand in glove with the motivation and satisfaction. Officer which discipline in working will be able to do the work productively. From other side the motivation, satisfaction work also have an effect on to discipline a officer in working. This research target is to prove the influence motivate and satisfaction work to discipline of officer of BAPPEDA of Pasaman regency. Method used with the double liner regression by research entire/ all officer of BAPPEDA of Pasaman regency as much 52 people. Result of this research give the public information and picture for the management that motivation and satisfaction work to have the impotant meaning in improving officer discipline. On that account discipline of officer of BAPPEDA of Pasaman regency more paying attention to and improving execution motivate and satisfaction work up at better again.